Superior 2-Year Functional Outcomes Among Young Female Athletes After ACL Reconstruction in 10 Return-to-Sport Training Sessions: Comparison of ACL-SPORTS Randomized Controlled Trial With Delaware-Oslo and MOON Cohorts. Issue 8 (1st August 2019) - Capin, Jacob J.; Failla, Mathew; Zarzycki, Ryan; Dix, Celeste; Johnson, Jessica L.; Smith, Angela H.; Risberg, May Arna; Huston, Laura J.; Spindler, Kurt P.; Snyder-Mackler, Lynn
Background: Outcomes after anterior cruciate ligament reconstruction (ACLR) are not uniformly good and are worse among young female athletes. Developing better rehabilitation and return-to-sport training programs and evaluating their outcomes are essential. Purpose: (1) Test the effect of strength, agility, plyometric, and secondary prevention (SAPP) exercises with and without perturbation training (SAPP + PERT) on strength, hops, function, activity levels, and return-to-sport rates in young female athletes 1 and 2 years after ACLR and (2) compare 2-year functional outcomes and activity levels among young female athletes in the Anterior Cruciate Ligament Specialized Post-Operative Return-to-Sports (ACL-SPORTS) trial to homogeneous cohorts who completed criterion-based postoperative rehabilitation alone (Multicenter Orthopaedic Outcomes Network [MOON]) and in combination with extended preoperative rehabilitation (Delaware-Oslo). Study Design: Randomized controlled trial, Level of evidence, 1; and cohort study, Level of evidence, 3. Methods: A total of 40 level 1 and level 2 female athletes were enrolled after postoperative impairment resolution 3 to 9 months after primary ACLR. Participants were randomized to 10 SAPP or SAPP + PERT sessions and were tested 1 and 2 years after ACLR on quadriceps strength, hop tests, functional outcomes, and return-to-sport rates. Participants were then compared with homogeneous cohorts of young (<25 years) female athletes who completed criterion-based postoperative rehabilitation alone (MOON) and in combination with extended preoperative rehabilitation (Delaware-Oslo) on 2-year functional outcomes. Results: No significant or meaningful differences were found between SAPP and SAPP + PERT, so groups were collapsed for comparison with the other cohorts. At 2-year follow-up, ACL-SPORTS had the highest scores ( P < .01) on the Marx activity rating scale (ACL-SPORTS, 13.5 ± 3.3; Delaware-Oslo, 12.5 ± 2.7; MOON, 10.6 ± 5.1); International Knee Documentation Committee Subjective Knee Evaluation Form (96 ± 7, 92 ± 9, and 84 ± 14, respectively); and Knee injury and Osteoarthritis Outcome Score (KOOS) subscales for Pain (98 ± 4, 94 ± 9, and 90 ± 10, respectively), Symptoms (94 ± 6, 90 ± 9, and 83 ± 14, respectively), Activities of Daily Living (100 ± 1, 99 ± 4, and 96 ± 7, respectively), Sports and Recreation (94 ± 8, 86 ± 15, and 82 ± 17, respectively), and Quality of Life (89 ± 14, 78 ± 18, and 76 ± 19, respectively). The Patient Acceptable Symptom State threshold on the KOOS–Sports and Recreation was achieved by 100% of the ACL-SPORTS cohort compared with 90% of Delaware-Oslo and 78% of MOON ( P = .011). Conclusion: Although perturbation training provided no added benefit, 10 sessions of return-to-sport training, compared with criterion-based postoperative rehabilitation alone, yielded statistically significant and clinically meaningfully higher 2-year functional outcomes among young, high-level female athletes after ACLR. Registration: NCT01773317 (ClinicalTrials.gov identifier).